2015
DOI: 10.1002/hed.24066
|View full text |Cite
|
Sign up to set email alerts
|

Locoregionally advanced nasopharyngeal carcinoma in childhood and adolescence: Analysis of 95 patients treated with combined chemotherapy and intensity‐modulated radiotherapy

Abstract: Neoadjuvant chemotherapy followed by IMRT with or without concurrent/adjuvant chemotherapy produced a superb treatment outcome in children and adolescents with stage III to IVB disease. Distant metastasis was the main failure. More effective treatment strategies are urgently needed to further improve the long-term survival. © 2015 Wiley Periodicals, Inc. Head Neck 38: E665-E672, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…A prospective, randomized study by Peng et al compared the outcomes and toxicities of IMRT vs. 2D-CRT for the treatment of NPC, and the result showed that better local recurrence-free survival and a lower incidence of toxicities can be achieved in the IMRT group for late-stage NPC patients (Peng et al 2012). In the current study, the NPC failure pattern was not altered by IMRT, and distant metastasis remained the major pattern of failure in paediatric and adolescent NPC, a result similar to the findings of other reports (Tao et al 2013; Guo et al 2015). The relatively short time to systemic failure in the absence of locoregional failure might suggest that subclinical metastasis that likely existed at first treatment required early systemic treatment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A prospective, randomized study by Peng et al compared the outcomes and toxicities of IMRT vs. 2D-CRT for the treatment of NPC, and the result showed that better local recurrence-free survival and a lower incidence of toxicities can be achieved in the IMRT group for late-stage NPC patients (Peng et al 2012). In the current study, the NPC failure pattern was not altered by IMRT, and distant metastasis remained the major pattern of failure in paediatric and adolescent NPC, a result similar to the findings of other reports (Tao et al 2013; Guo et al 2015). The relatively short time to systemic failure in the absence of locoregional failure might suggest that subclinical metastasis that likely existed at first treatment required early systemic treatment.…”
Section: Discussionsupporting
confidence: 92%
“…With better outcomes and longer survival, the prevention of radiation-induced complications becomes more important, and several studies have demonstrated quality of life advantages with IMRT in children with NPC (Tao et al 2013; Guo et al 2015). Laskar et al (2008) compared 2D-CRT with IMRT in 36 cases of paediatric and adolescent NPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, IMRT has provided excellent locoregional control in children and adolescent NPC patients with LRRFS of 95.2%. Nevertheless, the NPC failure pattern was not altered by IMRT, and distant metastasis remained the major pattern of failure, a result similar to the findings of other reports (5,35,36). We observed that a level of pretreatment EBV DNA >40,000 copies/mL was highly statistically significantly associated with the poorer DMFS and DFS.…”
Section: Discussionsupporting
confidence: 90%
“…However, studies that examined the use of IMRT in pediatric and adolescent NPC patients are limited [12,13]. In a recent study of locoregionally advanced NPC, 95 childhood and adolescence patients received combined CT (CDDP, Paclitaxel, Gemcitabine) and IMRT [14]. All the patients had been treated with neoadjuvant chemotherapy before IMRT with or without concurrent chemotherapy/adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%